Electronic properties of manganese impurities in germanium. (25th March 2015) - Lauwaert, J; Segers, S H; Moens, F; Opsomer, K; Clauws, P; Callens, F; Simoen, E; Vrielinck, H
Abstract: The electronic properties of manganese in crystalline germanium have been investigated by means of deep level transient spectroscopy (DLTS). Mn was diffused in the material by a thermal treatment at 700 °C. Next to the deep levels of nickel and copper, which are known contaminants in Ge treated at high temperature, three not previously reported levels were observed. These two hole and one electron traps, with apparent energy level positions at E V +0.136 eV, E V +0.342 eV and E C − 0.363 eV, were assigned to substitutional Mn. The analysis of the carrier capture cross-sections, the absence of field-assisted emission and the observation of the Mn 2− electron paramagnetic resonance spectrum in n-type Ge:Mn at low temperature are all compatible with Mn introducing two acceptor and one donor levels in the band gap of Ge.